394 STAFF AND PARENTS' PERCEPTIONS OF BARRIERS TO IMMUNIZATION FOR AFRICAN AMERICAN CHILDREN: A STUDY FROM PROS AND NMAPEDSNET. (1st January 2005) - Darden, P. M.; Blue, A. V.; Brooks, D. A.; Taylor, J. A.; Hendricks, J. W.; Bocian, A. B.
Abstract : Background: Even after controlling for socioeconomic status and source of care, African-American (AA) children are less likely to receive all of their recommended immunizations. Objective: To understand AA parent and pediatric office staff perspectives of barriers to immunization for AA children. Methods: Four pediatric practices with high AA patient populations from CA, FL, GA, and MD were selected to achieve a geographic and socioeconomic mix. Focus groups of AA parents who had children between the ages of 1 -3 were held. Separate focus groups were held with each practice's nonphysician office staff. A professional AA focus group facilitator conducted the sessions using guides developed by the research team. Findings from the sessions were transcribed, and research team members content analyzed results to develop common themes. Results: Parent focus groups had a mean of 10 (6-14) participants. Parent groups in each site differed dramatically from 100% Medicaid in CA to 80% private insurance in MD, family income 65% < $20K in CA to 30% > $75K in MD and marital status 67% single in CA to 90% married in MD. Staff focus groups had a mean of 4 (3-8) participants. Several themes emerged including lack of trust of the medical care system in general (although mothers trusted their child's doctor); delaying immunization because of mild illness; low priority on immunizations, including the perception they are only necessary for school or daycare entry; desire for parental control of the child's health care; family composition issues such as single-parent and blended families; and parental perception that some diseases are natural and need not be immunized against. A theme not supported by the parent focus group was a perception by staff of grandparent's control of health care. Conclusions: Identification of immunization barriers based upon AA parental and pediatric office staff perspectives provided critical information for an ongoing development of effective office-based interventions to address immunization disparities among AA children. These interventions will be tested in office practice.